Generation and characterization of three monoclonal antibodies useful in detecting and distinguishing bean golden mosaic virus isolates - Cancino, M; Abouzid, AM; Morales, Francisco José; Purcifull, DE; Polston, JE; Hiebert, E (Scientific Societies, 1995)
Two monoclonal antibodies prepared to purified virions of bean golden mosaic virus (BGMV) isolates from Guatemala (GA) and the Dominican Republic (DR) and one monoclonal antibody prepared to the coat protein of a BGMV isolate from Brazil (BZ) expressed in Escherichia coli were useful serological probes for detection of whitefly-transmitted geminiviruses. Abutilon mosaic, BGMV isolates from Puerto Rico (PR), and Homestead, Florida (H), BGMV-BZ, -DR, and -GA isolates, euphorbia mosaic, rhynchosia mosaic, squash leaf curl, soybean yellow mosaic, an isolate from Macroptilium lathyroides in Florida, and tomato mottle geminiviruses all reacted efficiently in Western blot and enzyme-linked immunosorbent assay with monoclonal antibody 3F7, indicating that this monoclonal antibody has a broad spectrum of reactivity. Another monoclonal antibody (2G5) reacted only with BGMV-DR, -GA, and -PR isolates. A third monoclonal antibody (5C5) reacted only with BGMV-BZ. A new geminivirus infecting cabbage (Brassicaceae) in Florida did not react with any of the three monoclonal antibodies.